PENGARUH VARIABEL SUMBER DANA PERUSAHAAN TERHADAP RENTABILITAS MODAL SENDIRI (Studi Pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia) - Wiwiek Kusumaning Asmoro (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2013)
This study aimed in determining influence of company’s funds sources on Return on Equity (ROE) for foods and beverages companies listed their shares in Indonesian Stock Exchange (IDX), based on their financial statements from the year 2007 until 2010 Variables used in this study comprises dependent variable, namely Return on Equity (ROE) and independent variables, i.e. intern and extern funds. Intern funds comprise Flowback Ratio while intern funds comprises The Debt to Total Capitalazition, Total Debt to Total Assets and Debt to Equity. Multiple linier regression with probability rate 0,05 indicated that: In first analysis (2007-2008), extern funds i.e. The Debt to Total Capitalazition, Total Debt to Total Assets, Debt to Equity and intern fund namely Flowback Ratio simultaneously had no significance influence on Return on Equity (ROE), it was proved by F calculate = -0,164 with significance rate 0,955 while in second analysis (2009-2010) all of independent variable i.e. intern and extern fund simultaneously had significant influence on Return on Equity (ROE) it was proved by F calculate = 20.701 with signification rate 0,000. Debt to Equity was independent variable which had dominant influence on Return on Equity (ROE) with significance rate 0,000 and t calculate = - 8.667. Conclusion, when economy’s condition was stable (2007-2008), the bigger company’s long term debt and retained earning would result the higher company’s Return on Equity. But when economy’s condition wasn’t stable (2009-2010) bigger long term debt would not rise Return on Equity while bigger retained earning would rise Returnd on Equity.